Intraspinal Mesenchymal Chondrosarcoma: Report of a Pediatric Case and Literature Review. (November 2017) - Di Giannatale, Angela; Colletti, Marta; Russo, Ida; Ferruzzi, Valentina; Anna, Vito Andrea Dell; Cozza, Raffaele; Colafati, Giovanna Stefania; Messina, Raffaella; Mastronuzzi, Angela; De Vito, Rita; Milano, Giuseppe Maria
Purpose: Mesenchymal chondrosarcoma (MCS) is an aggressive variant of chondrosarcoma and is a rare tumor, particularly within the pediatric population. Commonly, MCS originates in the bone, but it can also arise in extraskeletal sites, such as the brain and the intraspinal area. Due to the rarity of this tumor, there are no guidelines for its optimal treatment. Methods: We report a case of intradural extra medullary MCS, located at the T11–T12 level, in a 14-year-old male. The tumor was documented by magnetic resonance imaging and treated with gross total resection (GTR) without adjuvant treatment. We further reviewed the relevant pediatric literature and discussed the management and outcome of intracranial and intraspinal MCS. Results: The patient's follow-up showed no evidence of disease 2 years from diagnosis. A total of 51 cases of intracranial and intraspinal MCS have been reported (24 intraspinal and 27 intracranial). Recurrence has been described in only 4 patients with intraspinal MSC, and among them 3 received adjuvant chemotherapy and radiotherapy. GTR seems to reduce the risk of recurrence and, due to a higher cancer-mortality rate for these patients, adjuvant chemotherapy and radiotherapy are recommended in case aggressive surgery is not possible. Conclusions: According to our single experience, we would suggest that adjuvant therapy might be unnecessary in cases where a localized MCS undergoes GTR. Chemotherapy and radiotherapy should be recommended when GTR cannot be obtained. Further studies are needed to investigate a standard treatment approach for this rare tumor.